Some Fundamental Operations on Multimodal Networks in Biology. - Sioson, Allan A. (Philippine Computing Journal)
A multimodal network is a mathematical formalism based on hypergraphs that can model the informational, topological, and dynamic aspects of biological networks. In this paper, we discuss some fundamental operations on a multimodal network system. We also present how a multimodal network captures pertinent information from biology literature and how its structure and data can be stored in a relational database.